The macroeconomics of HIV/AIDS - Haacker, Markus; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The book is a comprehensive resource for public policymakers addressing the economic and fiscal consequences of the crisis. It is intended to bridge the gap between studies focused on the epidemic's impact on specific sectors, such as health and education, on the one hand, and broad national analyses on the other. Topics include welfare issues stemming from increased mortality rates and the effect of the epidemic at both microeconomic and the macroeconomic levels on economic growth and investment; education and accumulation of human capital; poverty and inequality; and public services, government finance, social security, and the health sector. The book gathers contributions by experts from many international organizations that are key players in the fight against HIV/AIDS and other institutions concerned with its social and economic consequences.
The demographic impact of HIV/AIDS / Brynn G. Epstein -- HIV/AIDS: the impact on the social fabric and the economy / Markus Haacker -- Thinking about the long-run economic costs of AIDS / Clive Bell, Shantayanan Devarajan, and Hans Gersbach -- AIDS and the accumulation and utilization of human capital in Africa / Nancy Birdsall and Amar Hamoudi -- The impact of HIV/AIDS on poverty and inequality / Robert Greener -- Welfare implications of HIV/AIDS / Nicholas Crafts and Markus Haacker -- The impact of HIV/AIDS on government finance and public services / Markus Haacker -- Financial effects of HIV/AIDS on national social protection schemes / Pierre Plamondon, Michael Cichon, and Pascal Annycke -- An economic assessment of Botswana's national strategic framework for HIV/AIDS / Iyabo Masha -- Impact of the HIV/AIDS epidemic on the health sectors of developing countries / Mead Over.
Includes bibliographical references.
rpm 15/11/13
Loans
Also available online.
Keywords: Acquired Immunodeficiency Syndrome -- Economics -- Statistics; HIV Infections -- economics -- Statistics; Demography -- Statistics; Developing Countries -- Statistics; Financing, Government -- statistics & numerical data